Assessing the Space-Time Structure with a Multidimensional Perspective - Olejnik, Alicja (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This study presents some remarks on procedure for space-time process investigation by the use of multidimensional panel spatial autoregressive model. It is shown that information on the strength and significance of the spatial interactions is given by the model. Motivation for the use of multidimensional dependence structure as well as some empirical examples are provided. It is argued that such approach could allow for more accurate description of the spatial dependence, whose true form often has a spatio-temporal character. It is emphasised that failure to recognise these multidimensional effects may lead to incorrect inference and therefore to biased conclusions.